Coffee wastewater treatment system in the Province of Rodríguez de Mendoza, Peru - Morales Rojas, Eli; Oliva Cruz, Segundo Manuel; Rascón Barrios, Jesús; Milla Pino, Manuel Emilio; Villegas Rivas, Dany Alberto; Chavez Quintana, Segundo Grimaldo (Revista Colombiana de Investigaciones Agroindustriales, 2020)
: Large volumes of coffee wastewater with a high content of organic matter are generated in the processing of coffee, causing impacts on the environment. That is why the objective of this work was to evaluate three systems of water treatment of coffee wastewater. A physical filter (sand, coal, river stone), a biological filter with water hyacinth (Eichhornia crassipes) and duckweed (Lemna minor L.) and a system with natural coagulants with moringa (Moringa oleífera L.) were compared. and prickly pear (Opuntia ficus-indica). Measurements were made every 15 days (between May and June 2019); data were processed in the R software. The results explain a linear discriminant function of 0.9355, indicating that the physical filter and the biological filter managed to reduce the parameters of Total dissolved solids (TDS) from 3,266 mg.L-1 to 2.55 mg.L-1 and phosphates (PO43¯) from 2,763 mg.L-1 to 0.975 mg.L-1, with a significant difference between treatments.